P629 Real-life treatment persistence and treatment outcomes of Finnish patients with Inflammatory Bowel Disease receiving vedolizumab as first-line biological treatment. (30th January 2023) - Ylisaukko-oja, T; Af Björkesten, C G; Erbel, A; Nuutinen, H; Jussila, A; Molander, P; Koskela, R; Blomster, T; Pajala, M; Ilus, T; Haiko, P; Kovac, B; et al.
Abstract: Background: Vedolizumab is a gut selective anti-lymphocyte trafficking monoclonal antibody directed towards the integrin α 4 β 7 . The efficacy and safety of vedolizumab in the treatment of adults with moderately to severely active Crohn's disease (CD) or ulcerative colitis (UC) are well-established in randomized clinical trials and real-world evidence studies. However, real-world data are limited on vedolizumab therapy used on biological naïve CD and UC patients. Here, we analyse treatment persistence, treatment outcomes, and reasons for treatment discontinuation of vedolizumab as a first-line biological treatment in CD and UC patients in a Finnish real-world setting. Methods: This was an observational, retrospective, multi-centre registry study. The cohort included all adult (≥ 18 years of age) patients with a diagnosis of CD or UC who initiated vedolizumab as a first-line biological treatment between May 2014, and June 2020, in the five Finnish university hospital districts. Clinical data were collected from electronic health records. The Prescription Register by the Finnish Social Insurance Institution was the data source for prescribed IBD treatments. Treatment persistence was defined as the time from initiation to discontinuation of therapy. P-values were calculated by using paired t -test. Results: The cohort consisted of 54 CD and 69 UC patients treated with vedolizumab as a first-line biological treatment. The mean ages were 61.9 and 56.8 years for CD and UC at the time of vedolizumab start, respectively. Disease duration was 10.9 years in CD and 10.5 years in UC. Altogether, 35.8% of patients had a history of cancer. At month 12, treatment persistence was 84.9% (n=44) in CD and 64.7% (n=41) in UC cohorts (Figure 1). Most vedolizumab discontinuations (CD, n=11; UC, n=26) were due to lack of efficacy, and treatment discontinuations due to adverse events were rare (n<5). Vedolizumab was associated with favourable treatment outcomes, as indicated by efficacy improvements at 12 months compared with baseline in Harvey-Bradshaw Index (CD, 3.2 vs 4.9, p=0.025), Partial Mayo Score (UC, 3.8 vs 5.1, p=0.021), Physician's Global Assessment (CD, 0.9 vs 1.8, p<0.001; and UC, 0.4 vs 2.1, p<0.001) scores, and positive endoscopic Mayo Score (UC, 0.7 vs 2.2, p<0.001) and biochemical outcomes. Conclusion: Vedolizumab showed high treatment persistence and positive treatment outcomes such as improvements in efficacy, endoscopic activity, and biochemical parameters when used as the first-line biological treatment.